Efficient Regulation of Environmental Health Risks - Lichtenberg, Erik; Zilberman, David (Quarterly Journal of Economics, 1988)
This paper introduces a decision framework for regulating environmental health risks which incorporates the characteristic uncertainty about the dissemination and toxicological impacts of environmental contaminants and the behavioral restrictions commonly encountered. Analysis indicates that increases in uncontrollable uncertainty will increase emphasis on average performance, that more potent or less controllable risks will be regulated more stringently and that increasing aversion to uncertainty may result in poorer average performance. The paper also develops an alternative measure for valuing risk of loss of life taking into account uncertainty about health risk generation processes.